2016
DOI: 10.1007/s00109-016-1388-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223 controls the expression of histone deacetylase 2: a novel axis in COPD

Abstract: Reduced activity of histone deacetylase 2 (HDAC2) has been described in patients with chronic obstructive pulmonary disease (COPD), but the mechanisms resulting in decreased expression of this important epigenetic modifier remain unknown. Here, we employed several in vitro experiments to address the role of microRNAs (miRNAs) on the regulation of HDAC2 in endothelial cells. Manipulation of miRNA levels in human pulmonary artery endothelial cells (HPAEC) was achieved by using electroporation with anti-miRNAs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…In another set of experiments, miR-223 was suggested to induce CX3CL1 mRNA level by regulating histone deacetylase 2 in human pulmonary artery endothelial cells (HPAECs) [52]. In human lung tissues from two cohorts of COPD patients, there were negative correlations between miR-223 and histone deacetylase 2 levels [52]. In another study, miR-181c regulated CCN1, which was upregulated in the lung tissues of CS-exposed mice as well as COPD patients [53].…”
Section: Copdmentioning
confidence: 98%
See 1 more Smart Citation
“…In another set of experiments, miR-223 was suggested to induce CX3CL1 mRNA level by regulating histone deacetylase 2 in human pulmonary artery endothelial cells (HPAECs) [52]. In human lung tissues from two cohorts of COPD patients, there were negative correlations between miR-223 and histone deacetylase 2 levels [52]. In another study, miR-181c regulated CCN1, which was upregulated in the lung tissues of CS-exposed mice as well as COPD patients [53].…”
Section: Copdmentioning
confidence: 98%
“…Furthermore, in a COPD rat model, cigarette smoke (CS) exposure elevated the concentrations of IFN-γ and TNF-α, increased the protein level of FAIM2, disrupted the lung architecture, and downregulated the level of miR-3202 [51]. In another set of experiments, miR-223 was suggested to induce CX3CL1 mRNA level by regulating histone deacetylase 2 in human pulmonary artery endothelial cells (HPAECs) [52]. In human lung tissues from two cohorts of COPD patients, there were negative correlations between miR-223 and histone deacetylase 2 levels [52].…”
Section: Copdmentioning
confidence: 99%
“…60 The expression levels of miR-223 significantly Moreover, miR-223 was also detected in human pulmonary artery smooth muscle cells (HPASMC), normal human bronchial epithelial cells (NHBEC), and human pulmonary artery endothelial cells (HPAEC), in the later especially at higher levels after stimulation by IL-1 and TNF-. 63 The authors identified histone deacetylase 2 (HDAC2) as a direct target of miR-223 in HPAEC, and demonstrated the potential disease promoting function of miR-223 during chronic obstructive pulmonary diseases. These findings together showcase the diverse function of miR-223 in nonmyeloid cells.…”
Section: Mir-223 In Adaptive Immunitymentioning
confidence: 99%
“…Decreases in global micro-RNA abundance were also observed in populations of alveolar macrophages from cigarette smokers (Graff et al, 2012). In contrast, Leuenberger and colleagues found that miR-223 was upregulated in the lungs of smokers (Leuenberger et al, 2016). Increased miR-223 correlated with decreased Histone deacetylase 2 (HDAC2) expression, which led to elevated expression of a pro-inflammatory chemokine, CX3CL1.…”
Section: Copdmentioning
confidence: 99%